2019
DOI: 10.1088/1758-5090/ab3582
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of step-gradient nanocomposite hydrogels for controlled cell migration

Abstract: In this study, we report the step-gradient nanocomposite (NC) hydrogel generated easily by spatial connection of different nanocomposite hydrogel pastes varying in the concentrations of nanomaterials with the aid of a 3D printing technique. The prepared 3D printed gradient NC hydrogel has self-adhesive properties and is used to direct the migration of fibroblast cells towards the higher concentration of biopolymer-coated silica-based nanomaterials (NMs) within the 3D network of the hydrogel. Furthermore, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
(72 reference statements)
0
16
0
Order By: Relevance
“…Control of precursor composition or of precursor combinations during 3D printing can be used to create gradients. The fabrication of a step-gradient nanocomposite hydrogel was reported by Motealleh et al [21]. Hydrogels were generated by the spatial connection of different nanocomposite hydrogel pastes, in which the concentration of nanomaterials was modulated by means of the 3D printing technique.…”
Section: D Printmentioning
confidence: 99%
“…Control of precursor composition or of precursor combinations during 3D printing can be used to create gradients. The fabrication of a step-gradient nanocomposite hydrogel was reported by Motealleh et al [21]. Hydrogels were generated by the spatial connection of different nanocomposite hydrogel pastes, in which the concentration of nanomaterials was modulated by means of the 3D printing technique.…”
Section: D Printmentioning
confidence: 99%
“…In addition, protein-related bone levels significantly increased with higher concentration of PMO in GradNC hydrogel. [53] These results suggested that the physical and biochemical gradients in hydrogel could be fine-tuned by bio-printing fabrication technique, and the fabricated gradient hydrogels could mimic the ECM of various cellular microenvironment.…”
Section: Bio-printingmentioning
confidence: 86%
“…Biosci. 2020, 20,1900300 TGF-ß1 [34] siRNA-PEI [41] PDGF-BB [42,43] VEGF158 [51] BP + cyt c [44] Migration of cell PMO [53] Cell attachment NCAD [39] RGD [34,46,50] IKVAV [40] HAV [50] Cell Gradient tissue formation Chondrocyte [52] Mimicking cancer environment U87MG cell [47] Materials and mechanical property…”
Section: Pmo Alglmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Several examples of an ionic crosslinked injectable alginate-based NC hydrogel for different applications have been reported from the Kehr's group. [36][37][38][39][40] Here, NC hydrogels were formed by Ca 2+ crosslinking of the negatively charged polysaccharide alginate and by incorporating periodic mesoporous organosilica (PMO) into the alginate network. The PMO surfaces were modified with polycations or with amino acids to achieve a positive charge on the PMO surfaces, thus allowing for a physical interaction with alginate.…”
Section: Physically Crosslinked Injectable Hydrogelsmentioning
confidence: 99%